Comparative Evaluation of Different Soil and Water Conservation Practices on Key Soil Physicochemical Properties along Slope Positions in the Belichamena Sub-Watershed, Central Ethiopia - Belayneh Bufebo; Aberash Tekalign; Abinet Tadesse (Journal of the Indian Society of Soil Science, 2026)
Soil erosion remains one of the most critical environmental challenges in Ethiopia. Despite the implementation of soil and water conservation (SWC) measures over the past two to three decades to curb and reverse this issue, erosion continues to affect many parts of the country, including the Ameka district. This study investigates the impact of soil and water conservation (SWC) practices on selected soil physicochemical properties across different slope positions in the Belichamena sub-watershed, Central Ethiopia. The study area encompassed both conserved and non-conserved cultivated lands situated along upper, middle, and lower slope positions. A total of 27 composite soil samples were collected and analyzed for parameters such as soil texture, moisture content, bulk density (BD), pH, soil organic carbon (SOC), soil organic matter (SOM), total nitrogen (TN), available phosphorus (AP), and electrical conductivity (EC), using standard laboratory procedures. To evaluate the impact of SWC interventions and slope position, statistical analysis was conducted using SPSS software version 26. The findings indicated that soils within bunds supported with desho grass (Pennisetum pedicellatum) exhibited higher levels of clay, moisture content, pH, SOC, SOM, TN, available phosphorus, and EC compared to adjacent bunds without desho grass and non-conserved plots. Conversely, higher bulk density, silt, and sand contents were observed in the non-conserved areas. Most soil properties showed statistically significant variation (p < 0.05) due to both conservation practices and slope position, except for silt, sand, and bulk density. Results indicated that SWC practices significantly enhanced soil fertility, particularly in lower slope positions, where greater accumulation of organic matter and nutrients was observed. Comparatively, non-conserved areas exhibited poorer soil structure and reduced nutrient levels. These results confirm that SWC practices are highly effective in mitigating soil erosion and enhancing soil quality in the Belichamena sub-watershed, thereby promoting sustainable agricultural productivity.